Berlin in fifty design icons / Sophie Lovell. - Lovell, Sophie, (Design museum (Conran Octopus Limited), 2017)
"Berlin's turbulent history has led to a wealth of innovative, evocative design, from the TV Tower and Jewish Museum to the S-Bahn and even kebab kiosks. Uncover this history and explore the fifty design icons that have shaped this city. One part design history, one part visual guidebook and with stunning photography selected by the Design Museum, Berlin in Fifty Design Icons is the perfect gift for design enthusiasts and anyone who loves Berlin." -- Provided by publisher.